Enhancing Students’ Civic Skills Through The Project Citizen Model And Creative Thinking Development - Ginting, Melly Andriani; Ndona, Yakobus; Ruslan, Dede (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study aims to examine the effect of the Project Citizen learning model and students’ creative thinking ability on the development of civic skills among seventh-grade students at SMP Negeri 3 Tigapanah. The research was motivated by the observed low level of students’ civic skills, which is partly due to the limited use of innovative learning models that foster active participation and creative thinking. The study employed a quasi-experimental method using a 2×2 factorial design. The sample consisted of two classes—VII-1 as the experimental group taught using the Project Citizen model, and VII-2 as the control group taught using the Teams Games Tournament (TGT) model. Data were collected through tests measuring civic skills and creative thinking ability. The results of the two-way ANOVA analysis show that: (1) students taught using the Project Citizen model achieved higher civic skills scores (mean = 75.65) compared to those taught using the TGT model (mean = 60.62); (2) students with high creative thinking ability outperformed those with low creative thinking ability in civic skills (mean = 87.85 vs. 69.55); and (3) there was a significant interaction between the learning model and creative thinking ability (F = 7.06, p 0.05). These findings indicate that the integration of the Project Citizen model and creative thinking development significantly enhances students’ civic competence by fostering critical, analytical, and participatory learning experiences. The study highlights the importance of adopting innovative, student-centered approaches in civic education to cultivate democratic and socially responsible citizens.